ANALISIS TINDAK TUTUR TRANSGENDER DALAM PODCAST YOUTUBE: KAJIAN KESANTUNAN BERBAHASA - Elma Zuwy Fadilla; Fildzah Mufidah; Indah Juli Hartika; Syafrina Zahra Assegaff; Tria Ningsih; M. Oky Fardian Gafari (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze transgender speech acts in Deddy Corbuzier’s YouTube podcast Close The Door, focusing on categories of speech acts and politeness strategies. The research employed a qualitative method, with data collected through documentation and transcription of selected episodes featuring transgender guests. The findings reveal that assertive speech acts dominate the conversation, followed by expressive, directive, and commissive acts. The speakers used language to assert identity, express emotions, provide advice, and build commitment. Politeness strategies identified include positive politeness, negative politeness, wisdom, and face-saving acts, which serve to maintain self-image and reduce social stigma. In conclusion, language functions not only as a tool of communication but also as an instrument of identity negotiation, enabling transgender individuals to construct counter-narratives against stereotypes in digital public spaces.